Uso de Nivolumab en pacientes con recaída postrasplante alogénico de progenitores hematopoyéticos en enfermedad de Hodgkin, reporte de dos casos clínicos - Carvallo, Cristan; Negrete, Francisca; Morales, Romina; Lobos, Nataly; Rojas, Marcos; Jara, Kathy; Schüler, Constanza; Vidal, Martin; Garnham, Nicolás; Mosso, Claudio (Revista Médica de Chile, 2021)
Hodgkin’s Lymphoma has a very good prognosis. In the unusually refractory patients allogeneic transplantation offers a chance of cure. The so-called checkpoint inhibitors, such as Nivolumab can play a relevant role in this type of patients. Their side effects and usefulness after allogeneic transplantation are under investigation. Relapse after allogeneic transplantation has an extremely poor prognosis. We report two patients with refractory Hodgkin’s lymphoma who relapsed after an allogeneic transplant and who were successfully treated with Nivolumab.